2006
DOI: 10.1158/0008-5472.can-06-1239
|View full text |Cite
|
Sign up to set email alerts
|

Nelfinavir Down-regulates Hypoxia-Inducible Factor 1α and VEGF Expression and Increases Tumor Oxygenation: Implications for Radiotherapy

Abstract: The phosphatidylinositol 3-kinase (PI3K)/Akt pathway can increase vascular endothelial growth factor (VEGF) and hypoxia-inducible factor 1A (HIF-1A) expression. We examined the effect of nelfinavir, an HIV protease inhibitor that inhibits Akt signaling, on VEGF and HIF-1A expression and on angiogenesis, tumor oxygenation, and radiosensitization. Nelfinavir decreases VEGF expression under normoxia via the transcription factor Sp1, which regulates the proximal core VEGF promoter. Nelfinavir decreased Sp1 phospho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(146 citation statements)
references
References 39 publications
5
139
0
Order By: Relevance
“…As discussed below, many studies testing the effects of antiangiogenic drugs have shown a presence of a "normalization window"-a time period beginning with the appearance of a normalized vascular phenotype (typically within 1 -2 days of starting treatment), and ending when features of normalization are lost Winkler et al 2004;Jain 2005b;Batchelor et al 2007;Kamoun et al 2009 Xian et al 2006;McCarty et al 2007;Mazzone et al 2009. c This is controversial given recent reports of increased metastasis after antiangiogenic therapy in certain animal models (Ebos et al 2009;Paez-Ribes et al 2009 Gorski et al 1999;Hansen-Algenstaedt et al 2000;Lee et al 2000;Kozin et al 2001;Ader et al 2003;Winkler et al 2004;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006a;Dings et al 2007;Kashiwagi et al 2008;Batra et al 2009;Cerniglia et al 2009;Tsukada et al 2009;McGee et al 2010. g Teicher et al 1995a,b;Wildiers et al 2003;Segers et al 2006;Dickson et al 2007a,b,c;Bhattacharya et al 2008Bhattacharya et al , 2009Zhou et al 2008;Juan et al 2009;Zhou and Gallo 2009;J Liu, S Liao, B Diop-Frimpong, et al, unpubl. data. section, we discuss the key molecules implicated in tumor vessel biology with a focus on their role in regulating vascular normalization.…”
Section: Evidence For Vascular Normalization In Tumors Preclinical Evmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed below, many studies testing the effects of antiangiogenic drugs have shown a presence of a "normalization window"-a time period beginning with the appearance of a normalized vascular phenotype (typically within 1 -2 days of starting treatment), and ending when features of normalization are lost Winkler et al 2004;Jain 2005b;Batchelor et al 2007;Kamoun et al 2009 Xian et al 2006;McCarty et al 2007;Mazzone et al 2009. c This is controversial given recent reports of increased metastasis after antiangiogenic therapy in certain animal models (Ebos et al 2009;Paez-Ribes et al 2009 Gorski et al 1999;Hansen-Algenstaedt et al 2000;Lee et al 2000;Kozin et al 2001;Ader et al 2003;Winkler et al 2004;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006a;Dings et al 2007;Kashiwagi et al 2008;Batra et al 2009;Cerniglia et al 2009;Tsukada et al 2009;McGee et al 2010. g Teicher et al 1995a,b;Wildiers et al 2003;Segers et al 2006;Dickson et al 2007a,b,c;Bhattacharya et al 2008Bhattacharya et al , 2009Zhou et al 2008;Juan et al 2009;Zhou and Gallo 2009;J Liu, S Liao, B Diop-Frimpong, et al, unpubl. data. section, we discuss the key molecules implicated in tumor vessel biology with a focus on their role in regulating vascular normalization.…”
Section: Evidence For Vascular Normalization In Tumors Preclinical Evmentioning
confidence: 99%
“…As a consequence, inhibitors of oncogene activity can indirectly normalize tumor vessels, potentially enhancing not only the action of chemotherapy and radiotherapy, but also their own antitumor cell activity. Investigators have reported various aspects of normalization in response to inhibition of several oncogenes including HER-2 (Izumi et al 2002), the PI3K-AKT-mTOR axis (Pore et al 2006a;Schnell et al 2008;Xue et al 2008;Qayum et al 2009), Ras (Cohen-Jonathan et al 2001Delmas et al 2003;Qayum et al 2009), and the epidermal growth factor receptor (EGFR) (Cerniglia et al 2009;Qayum et al 2009;Johns et al 2010). In the case of HER-2, we have shown that treatment of leptomeningeal HER-2 positive breast cancer with trastuzumab (a monoclonal antibody directed against HER-2) not only inhibits tumor cell proliferation, but also normalizes vessels.…”
Section: Indirect Inhibitors Of Angiogenesismentioning
confidence: 99%
“…Our results corroborated with Pore et al, who demonstrated that nelfinavir, another HIV protease inhibitor, interfered with HIF-1a protein translation in carcinoma cells. 38 An active PI3K/Akt pathway is required for hypoxia-induced expression of HIF-1a protein translation. 39,40 Hence, a preliminary study was performed to analyze the levels of Akt in RPE cells post treatment with ritonavir.…”
Section: Discussionmentioning
confidence: 99%
“…27) HIF-alpha activation is mediated by its stabilization via the Akt/PI3kinase signaling pathway. 28) Akt/PI3kinase is a major kinase involved in the down-stream signaling pathway of the CCK-2/gastrin receptor. 29,30) Thus, gastrin is a likely mediator of HIF-alpha activation or VEGF expression.…”
Section: Discussionmentioning
confidence: 99%